Comparative genomics of Leishmania braziliensis promastigotes subjected to different temperatures (2019)
The leishmaniases are complex neglected diseases caused by the protozoan parasite Leishmania. Cutaneous leishmaniasis is the most common clinical manifestation around the world, and in the Americas the main aetiological agent is Leishmania braziliensis. In recent studies, chromosome and gene copy number variations (CNVs) have been highlighted as some mechanisms used by Leishmania species to adapt to environmental changes such as host change or drug pressure. However, no studies have described the impact of temperature shifts across the genome of Leishmania promastigotes and particularly in L. braziliensis. Therefore, we sequenced the genome (DNA-Seq) of L. braziliensis promastigotes from cultures subjected to three different temperatures, 24, 28, and 30°C; then, we analysed the aneuploidy, gene CNVs, SNPs and Indels compared with those at the control temperature (26°C). We found that the increase in temperature at 30°C had a negative effect on promastigotes proliferation; although, there were no changes in the somy, SNPs and Indels on the DNA among the three temperatures compared to the control. Only around 3% of the genes having significant copy number variation (CNVs) at each temperature showed some important genes for adaptation to temperature shifts. In conclusion, there is not a relevant genome response to the temperature shift in short-term, therefore the adaptation of this species to abiotic change could be occurring at transcriptome level. The ecological consequences are herein discussed.